2007
DOI: 10.1017/s1368980007246695
|View full text |Cite
|
Sign up to set email alerts
|

Educational variations in the consumption of foods containing fat in Finland and the Baltic countries

Abstract: Objective: To examine educational differences among people who consume foods containing fat in Finland and the Baltic countries. Design: Data were collected from cross-sectional postal Finbalt Health Monitor surveys that were carried out in 1998, 2000 and 2002. Setting: Estonia, Finland, Latvia and Lithuania. Subjects: For each survey, nationally representative random samples of adults aged 20 -64 years were drawn from population registers (Estonia, n ¼ 3656; Finland, n ¼ 9354, Latvia, n ¼ 6015; Lithuania, n ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
14
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
6
14
1
5
Order By: Relevance
“…Social differences in milk consumption did not change over time. Such results are in line with other studies that reported an inverse association between consumption of high-fat milk and education level [36-38]. …”
Section: Discussionsupporting
confidence: 93%
“…Social differences in milk consumption did not change over time. Such results are in line with other studies that reported an inverse association between consumption of high-fat milk and education level [36-38]. …”
Section: Discussionsupporting
confidence: 93%
“…In previous studies, the consumption of cheese has been more common among persons with a higher educational position in Finland and in several other countries (Petkeviciene et al 2007;Prättälä et al 2003;SanchezVillegas et al 2003). Cheese is typically an expensive food and its consumption is likely to be more common among persons in higher socio-economic groups in Russia as well.…”
Section: Discussionmentioning
confidence: 90%
“…Their use has decreased remarkably in Finland thereafter. Several Finnish studies have demonstrated that Finns with lower socio-economic position use more dairy fat (Leino et al 1999;Petkeviciene et al 2007). This study draws on data that allow a comparison between two neighbouring areas, the district of Pitkäranta in the Republic of Karelia, Russia and North Karelia in Finland.…”
Section: Introductionmentioning
confidence: 99%
“…All three indicators of SEP have shown to be associated with dietary habits (Johansson et al, 1999;Mishra et al, 2002;Perrin et al, 2002;Robinson et al, 2004;Metcalf et al, 2006;Lallukka et al, 2007;Petkeviciene et al, 2007;Arkkola et al, 2008). Previous studies most often use only one or two of the indicators.…”
Section: Introductionmentioning
confidence: 99%